Mila 18 - Uris, Leon, 1924-2003 (Doubleday, 1961)
Mila 18 was the command post of the resistance movement organized by the Warsaw Jews. This is the story of the handful of men and women who, knowing they had to die, defied the whole German Army with their homemade weapons and bare hands.